Use of the digital CAD-CAM system in dentists at the Universidad Privada de Huancayo Franklin Roosevelt, 2023 - Zavaleta Alemán , Liliana Melchora (2024)
Objective: Determine the prevalence of the use of the digital CAD-CAM system in dentists at the Universidad Privada de Huancayo Franklin Roosevelt, 2023. Material and Methods: Basic descriptive, cross-sectional, prospective and observational research study. The sample was made up of 16 teaching dental surgeons from the Franklin Roosevelt Private University of Huancayo. The data collection instrument was a questionnaire, prepared in-house and validated by expert judgment, with 20 questions whose main objective was to collect information regarding sociodemographic factors and the use of CAD/CAM to later be statistically analyzed. Results: The prevalence of the use of the digital CAD-CAM system in dentists at the Franklin Roosevelt Private University of Huancayo is 43.8% of the total evaluated; Depending on sex, only 46.1% of men and 33.3% of women use the CAD-CAM system; Depending on age, 44.6% of the 31 to 49 year-old group, and 42.9% of dentists aged 50 and over use the system. The level of knowledge of the CAD-CAM digital system was high in 68.8% of the dentists, moderate in 18.7% and low in 12.8%. Keeping up to date with technology (57.1%) and improving the quality of treatments (42.9%) are the main reasons for using the system; while the reasons for not using the digital CAD-CAM system with the highest prevalence were high costs (77.8%) and the need to have a lot of knowledge of the system's technology (22.2%). Finally, 100% of dentists state that the digital CAD-CAM system has an important role in the future of dentistry. Conclusions: It concludes that 43.8% of dentists at the Franklin Roosevelt Private University of Huancayo, 2023 use the digital CAD-CAM system.